Pengaruh Likuiditas, Profitabilitas dan Leverage Terhadap Financial Distress pada Perusahaan Sektor Transportasi - Putri Dwi Oktaviani; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to analyze the effect of liquidity, profitability, and leverage on financial distress. This study uses quantitative data. The population in this study were all transportation companies listed on the Indonesia Stock Exchange (IDX) in the period 2016 - 2019. The sample selection method used purposive sampling method and obtained the number of research samples as many as 26 companies with a total of 104 observational data. The data analysis in this study used the Eviews version 10. The results showed that liquidity with the current ratio proxy had an effect on financial distress conditions. Profitability with the return on assets (ROA) proxy has no effect on financial distress and leverage with the debt ratio proxy has no effect on financial distress.